A Novel Missense Mutation in Two Families with Congenital Plasminogen Deficiency: Identification of an Ala675 to Thr675 Substitution - Mima, N; Azuma, H; Shigekiyo, T; Saito, S (Thrombosis and Haemostasis, 1996)
We used a polymerase chain reaction (PCR) strategy and restriction fragment polymorphism analysis to evaluate all 19 exons of the plasminogen (PLG) gene in a Japanese patient with congenital PLG deficiency and her family members (family C). Sequence analysis following amplification of each exon and its flanking regions showed a single G to A transition in exon 17, resulting in the conversion of an Ala675 codon (GCT) to Thr675 codon (ACT). Since this mutation generates a new Mae III site, the Mae III digestion patterns of the PCR-amplified exon 17 fragments from each family member were analyzed. In all cases, the patterns correlated with the activities and antigen levels of plasma PLG in those members. The identical G to A transition in the same codon of exon 17 was detected by a Mae III digestion experiment in another proband and her family members with congenital PLG deficiency (family K). Furthermore, 20 normal individuals examined had no Mae III restriction site at this location. We conclude that a G to A transition in exon 17 is responsible for the congenital PLG deficiency inherited in these two Japanese families.